Penerapan Metode ABC Indeks Kritis dalam Pengelolaan Persediaan Obat di Instalasi Farmasi Rumah Sakit XYZ Pekanbaru, Riau Tahun 2018 - Susanto, Monika Noviera; Permanasari, Vetty Yulianty (UI Scholars Hub, 2019)
The process of making the XYZ Hospital formulary by the Therapy Pharmacy Team (TFT) has not considered the critical level of a medicine for patients. The failure to carry out the assessment has caused an unplanned purchase of the medicine that needed immediately and affecting patient safety. The ABC method can identify drugs that must always be available and worth a large investment. There is no cost control of drug supplies at XYZ Hospital because data on the value of investment in drugs have not been analyzed. This study uses a qualitative research design by applying the ABC index critical method to data on drug needs in 2018. The research data was obtained through in-depth interviews, observation and review of planning documents and drug procurement. 82% of the drugs in the warehouse are rarely used, but 53 of them are drugs that have high investment value that require special attention. Drugs that have the largest 5 (five) investment values but are very rarely used (group C usage value) are: Albuminar 25%, Octalbin 25%, Terfacef injection, Trijec 1 gram and Lanmer injection.The next XYZ Hospital formulary must issue 530 types of drugs that are not critical and have no use. The smaller number of types of drugs that enter the formulary will facilitate the process of control and storage of inventory